ANALISIS FAKTOR KEBERHASILAN INSEMINASI BUATAN TERNAK SAPI POTONG DI KECAMATAN TOMBOLO PAO KABUPATEN GOWA - Hifizah, Amriana; Astati, Astati (Teknosains: Media Informasi Sains dan Teknologi, 2015)
The enhancement of the implementation of Artificial Insemination program is one of the government's efforts to boost the cattle’s population in Indonesia, especially the eastern part of Indonesia. Gowa Regency through the Department of Fisheries and Livestock has been implementing Artificial Insemination (AI), especially in District of Tombolo Pao which has been running for 3 years. This study was conducted to see how far the success rate of AI in District of Tombolo Pao by looking at the influence of several factors: the origin and quality of the frozen semen used, the farmers’ characteristics, the inseminator qualifications, S/C ratio, Conception Rate (CR) and Calving Interval (CI). This study was conducted from June to August 2014 in District of Tombolo Pao, Gowa Regency. The basic method used is descriptive and quantitative analysis. The data used is primary and secondary data. This study aims to analyze the factors that support the success of AI in District of Tombolo Pao, Gowa Regency, they are: The origin and quality of frozen semen used; Characteristics of the farmers; the Farmers’ participation on AI; and the success of AI based on the score of Conception Rate (CR), S / C ratio, and Calving Interval (CI). Frozen semens used in AI in District of Tombolo Pao are from the Center of AI in Lembang and Singosari, West Java. The quality of the semen also can be determined from the score of conception rate which is 60-75%. The characteristics of the respondent farmers: the majority age is 30-50 years (75%), most of the farmers’ background is elementary education level (70.5%), with the main livelihood as farmers (79.6%) having averagely 4 -5 cattles (68.2%) and the average period of being a cattle farmer is 7-8 years (86.4%). Participation of farmers in the AI program is very enthusiastic indicated by 79.5% of the farmers agree for crossing their cattle breed through AI technique. The period of the farming, number of livestock and the participation of the farmers in AI program is not significantly influenced the success of AI. However, the success of AI program can be figured out through the score of CR = 60-75% (84.1%); S / C ratio <3 (75%); and CI average of 12 months (70.5%). The age of the farmers is significantly influenced the success 14 of AI in CI score (p <0.05). Level of education significantly influenced the success of AI in CR score (p <0.05).